(3efXheI aj GdJhbjJs - (3CHh RjO YHO GdQMef Hf YHO GdbGOQ Hf Ydj Hf CHi GdeMGSf Hf jhSa GdaGSis ((3KZQ WfLI s)
(3ChdgG (B:s
(3GdMeO ddg GdPi bO LYdG JYde JbOjQ GdReGf SHdG Ke GdUdGI hGdSdGe GHOG Mhd GdReGf OGFekG eLOOkG s
(3BNQgG (B:s
(3hjSCd Gddg LejY GdZaQGf YHOc GdaGSi YHO GdQMef eSJTaYkG HGdeUWai NjQ GdGfGe Ydjg GaVd GdUdGI hGdSdGe GfJgJ HMeO Gddg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGdKs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B612 ; (3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B694 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B2 s
(3JHUQGJ GdCUd (B:s
Keywords: (3Gdadcs